Assessing Tourism Potential In Bhaktapur Durbar Square, Nepal - Neupane, Ramesh; KC, Anup; Pant, Ramesh Raj (International Journal of Environment, 2013)
Tourism is one of the most promising driver and contributor of the world economy having significant role in sustainable development, economic upliftment and social benefits. It has the potential to contribute towards environmental protection and poverty reduction. Prior to investment in tourism, concerned authorities must know the condition of respective tourist resources, their attractiveness and levels of touristic demand. Very few studies in Nepal have made an effort to quantify the tourism potential in cultural, historical and religious sites such as Bhaktapur Durbar Square. With an objective to assess the tourism potential of Bhaktapur Durbar Square using Weighted Sum Method, this study was carried out from start of June to the end of July in 2013. For this purpose, questionnaire survey with tourists, private businesses and public sector institutions; focus group discussion and key informant interview with tourism enterpreneur and local government officer was carried out. The tourism potential was found to be high with a strength of exceptionally rich cultural, historical and religious heritage, favourable geographical situation, positive image of local Newari food products and friendly and welcoming local people. The areas of weaknesses were lack of tourism infrastructures and services, lack of tourist information and weak management of tourist area. Hence, to utilise the tourism potential of Bhaktapur Durbar Square to the fullest for the economic upliftment of its inhabitants, promotional activities such as tourism fairs, festivals, cultural dances and events should be conducted at regular intervals with prompt security services. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 250-261 DOI: http://dx.doi.org/10.3126/ije.v2i1.9225